Facilitators and barriers to community-based HIV testing in Guinea: a CFIR-based implementation analysis - Soriba Camara; Soriba Camara; Tamba Mina Millimouno; Tamba Mina Millimouno; Mory 1 Kourouma; Mory 1 Kourouma; Abdoulaye Sow; Sidikiba Sidibé; Aly Badara Touré; Aly Badara Touré; Aly Badara Nabé; Alexandre Delamou; et al. (Frontiers in Public Health)
IntroductionIn Guinea, where 36% of people living with HIV (PLHIV) are unaware of their serostatus, innovative screening strategies are crucial to achieving the joint United Nations Program on HIV/AIDS’ 95–95-95 targets. Community-based HIV testing, as recommended by the World Health Organization, aims to reach at-risk populations by leveraging local resources and actors. Using the Consolidated Framework for Implementation Research (CFIR), this study assessed facilitators and barriers to implementing community-based HIV screening across 10 pilot sites in Guinea, with the goal to optimizing its effectiveness.MethodsThis qualitative descriptive study applied the CFIR framework to identify factors influencing the implementation of community-based HIV screening and capture the nuanced perspectives of stakeholders. Overall, 28 in-depth interviews were conducted with key participants, including PLHIV, health workers, community-based actors, and members of the national coordination teams.ResultsHome-based testing was identified as a key facilitator for improving access to healthcare by reducing financial and logistical barriers. However, several barriers hindered its effectiveness, including frequent stock shortages, concerns about confidentiality and stigma, insufficient training and incentives for community counselors, and the absence of clear protocols defining the roles and responsibilities of stakeholders.ConclusionThe findings emphasize the need to strengthen community-based HIV testing in Guinea by ensuring a consistent supply of essential resources, enhancing coordination among stakeholders, and providing adequate incentives for community counselors. Integrating this approach into national policies could enhance both its effectiveness and sustainability, offering actionable insights for adapting HIV testing strategies in similar resource-limited settings.